Strategic integration of corporate sustainability in the ski resort industry with attention to climate change - Puranen, Visa (My University, 2023)
Global warming and climate change are causing more distress on the world and on certain industries. One industry that is in a particularly vulnerable position is the ski resort industry, that relies on cold temperatures and sufficient snowfall. As winter seasons are becoming shorter and yearly amount of snowfall is decreasing, ski resort industry is facing alarming threats in the near future. Thus, sustainability issues have been rising trends within ski resorts. Interest in sustainability has increased among governments, the public and organizations. Researchers and managers have started focusing more on corporate sustainability, its impacts, practices and management. For long, corporate sustainability was seen as a separate entity from an organization’s strategy, but lately its strategic importance and value has been given more focus. It has become clear that in order to create true sustainable and economic value from corporate sustainability, it has to be incorporated with strategic management. Strategic corporate sustainability management in research is suggested to be a phased process, where the step-by-step nature of the process reminds closely of other strategy processes. It starts with management initiation and includes the strategic phases of normative positioning, determining contextual factors, strategic planning and operational management. The findings of this study suggest that corporate sustainability should be integrated into the organization’s strategy by integrating sustainability practices to all corporate functions. It is suggested that corporate sustainability can be framed by business model innovation, as both processes include critical similarities. The findings also suggest that management motivations have a large impact on how climate change threats are viewed. Thus, having large impacts on organization’s sustainability practices. It became clear that motivations and views differ significantly even as climate change threats in the literature have been viewed to affect most parties in the ski industry.

Ilmaston lämpeneminen ja ilmastonmuutos aiheuttavat kasvavaa huolta maailmalla ja tietyillä toimialoilla. Hiihtokeskus toimiala on erityisen haavoittuvassa asemassa, koska se turvautuu kylmiin olosuhteisiin ja riittävään lumisateeseen. Hiihtokeskus toimiala kohtaa tulevaisuudessa hälyttäviä uhkia, kun talvet lyhenevät ja lumisateiden määrä vähenee. Tämän vuoksi kestävä kehitys on yksi hiihtokeskuksien trendeistä. Mielenkiinto kestävyyttä kohtaan on kasvanut hallituksissa, yleisössä ja organisaatioissa. Tutkijat ja managerit ovat alkaneet kiinnittää lisää huomiota yritysten kestävään kehitykseen, sen vaikutuksiin, harjoitteisiin ja johtamiseen. Pitkään yrityksen kestävää kehitystä (CSM) pidettiin erillisenä toimintona organisaation strategiasta, mutta viime aikoina sen strateginen merkittävyys ja arvo ovat saaneet lisää huomiota. On tullut selväksi, että luodakseen todellista kestävää ja taloudellista arvoa, yrityksen kestävä kehitys pitää liittää strategiseen johtamiseen. Kirjallisuus ehdottaa yrityksen kestävän kehityksen strategista johtamista vaiheittaisena prosessina, jonka porrasteinen luonto muistuttaa muita strategia prosesseja. Prosessi alkaa johdon alullepanolla ja sisältää strategiset vaiheet kuten normatiivisen asemoinnin, strategiaa ympäröivien vaikuttavien tekijöiden määrittelyn, strategisen suunnittelun ja operatiivisen johtamisen. Tämän tutkimuksen tulokset osoittavat, että yrityksen kestävän kehityksen strateginen integrointi yrityksen toimintaan ja strategiaan tapahtuu operatiivisella tasolla yrityksen toiminnoissa ja päivittäisessä toiminnassa. Tutkimus viittaa, että kestävä kehitys voidaan yhdistää yrityksen liiketoimintamallien innovointiin molempien prosessien samanlaisuuksien vuoksi. Tutkimuksen tulokset viittaavat myös siihen, että johdon motivaatioilla on suuri vaikutus siihen, miten ilmastonmuutoksen tuomat uhkakuvat vaikuttavat yrityksen toimintaan. Vaikka kirjallisuus ja tutkimukset luovat kuvaa missä ilmastonmuutos vaikuttaa hiihtokeskus toimialalla lähes kaikkiin osapuoliin, näkemykset ja motivaatiot silti vaihtelevat.
Keywords: fi=Kansainvälinen liiketoiminta|en=International Business|; Master’s Programme in Strategic Business Development